BIM-based government engineering quality supervision system - Shuqiang Wang; Jinping Yu (Journal of Asian Architecture and Building Engineering)
In this paper, an engineering quality supervision system with integrated BIM and multiple IT technologies is developed to improve the level and efficiency of engineering quality supervision through a microservice architecture design, realizing the cloud storage management and strong scalability of a large amount of supervision record information data. A BIM model lightweight solution is proposed, data mapping is established between the model and quality supervision work procedures, and the interactive application of the model and business processes is realized. In system regulatory process management, two guidance methods are developed to meet the requirements of easy working and efficient collaboration among stakeholders. The system is developed and applied to a practical project in a management station, where it is shown to simplify the workflow and improve the efficiency of project approval.